Association Between Domain-Specific Physical Activity and Chronic Low Back Pain in Community-Dwelling Older Adults: a Cross-Sectional Study - Silva Martins, Michael Douglas da; Lemes, Italo Ribeiro; Esposito, Eleonora; Morelhao, Priscila Kalil; Narciso, Pedro Henrique [UNESP]; Franco, Marcia Rodrigues; Pinto, Rafael Zambelli (Human Kinetics Publ Inc, 2023)
To investigate the association between physical activity (PA) domains and chronic low back pain (LBP) in older adults. A crosssectional study where sociodemographic, behavioral, and health variables; PA; and presence of chronic LBP were collected. Higher scores of PA defined the more active participants. Binary logistic regression was used to test the association between PA domains and chronic LBP. A total of 516 participants were included. The mean age was 71.8 (95% confidence interval, CI, [71.1, 72.5]) years, and 29%, 27%, 25%, and 31% were identified as more active in the household, sports, leisure-time, and total PA domains, respectively. More active participants in sports (odds ratio = 0.62, 95% CI [0.40, 0.97]), leisure-time (odds ratio = 0.54, 95% CI [0.35, 0.85]) and total (odds ratio = 0.60, 95% CI [0.39, 0.92]) PA domains were less likely to report chronic LBP. High levels of sports, leisure-time, and total PA were inversely associated with chronic LBP.
Keywords: aging; chronic pain; epidemiologic study